موقف شيشرون من الكهانة: دراسة تحليلية نقدية - محمود، مصطفى رمضان مصطفى (الجمعية الفلسفية المصرية, 2022)
جاء هذا البحث بهدف إلقاء الضوء على جانب في غاية الأهمية؛ ألا وهو موقف شيشرون من الكهانة، ويعد شـيشرون Cicero (١٠٦ ق.م- ٤٣ ق.م)، فيلسوفا وخطيبا رومانيا، امتاز بأسلوبه النقدي، وله مؤلفات كثيرة، منها: «عن طبيعة الآلهة»، و«عن القدر»، و«عن العرافة أو الكهانة»، و«الجمهورية» الذي استعار اسمه من جمهورية أفلاطون، وجمع فيه أهم المذاهب السياسية. وتعنى الكهانة أو التكهن: ادعاء علم الغيب، والكاهن هو الذي يخبر عن بعض الأحداث، فيصيب بعضها، ويخطئ أكثرها، ومن الألفاظ التي تشير إلى الكاهن: العراف، والمنجم الذي يخبر عن المستقبل بطلوع النجم وغروبه، وسوف نتناول في هذا البحث موقف حضارات الشرق القديم من التكهن، ولاسيما عند كل من: الأشوريين، والكلدانيين، والمصريين القدماء، كما سوف نعرض لنماذج من فلاسفة اليونان الذين اعتقدوا بالتكهن أمثال: سقراط، وأفلاطون، والرواقيـة، فضلا عن أدلتهم على صحة الاعتقاد به، كما سوف نوضح في هذا البحث موقف شيشرون بصدد الكهانة؛ وذلك عن طريق تفنيده آراء السابقين عليه." This Research came with the aim of shedding light on a very important aspect; namely, Cicero's Attitude on Divination, and Cicero (106 BC- 43 BC), is a Roman Philosopher and Orator, distinguished by his critical style, and has several books, including: «On the Nature of the Gods», )On Fate(, «On the Divination», and (The Republic( which borrowed its name from Plato's Republic, and collected in it the most important Political doctrines. Divination means: Claiming knowledge of the unseen, and the Diviner is the one who informs about some events, and he is correct in some of them, and most of them are wrong, Among the words that refer to the Diviner are: Clairvoyant, and Astrologer who tells about the Future with the rising and sunset of the star, and we will discuss in this Research the attitude of the ancient civilizations of the East on Divination, especially: the Assyrians, the Chaldeans, and the ancient Egyptians, we will also show examples of Greek Philosophers who believed in Divination, Such as: Socrates, Plato, Stoicism, as well as their evidences for the validity of belief in it, We will also explain in this Research Cicero's Attitude on Divination; by objection the opinions of his Predecessors."
Keywords: الفلسفة اليونانية -- التكهن -- علم الغيب -- القضاء والقدر -- شيشرون، ماركوس توليوس سيسرو، ت. 43 م